LFA-1 in T Cell Migration and Differentiation - Walling, Brandon L.; Kim, Minsoo (Frontiers in Immunology, 2018)
Maintenance of homeostatic immune surveillance and development of effective adaptive immune responses require precise regulation of spatial and temporal lymphocyte trafficking throughout the body to ensure pathogen clearance and memory generation. Dysregulation of lymphocyte activation and migration can lead to impaired adaptive immunity, recurrent infections, and an array of autoimmune diseases and chronic inflammation. Central to the recruitment of T cells, integrins are cell surface receptors that regulate adhesion, signal transduction, and migration. With 24 integrin pairs having been discovered to date, integrins are defined not only by the composition of the heterodimeric pair, but by cell-type specific expression and their ligands. Furthermore, integrins not only facilitate adhesion but also induce intracellular signaling, and have recently been uncovered as mechanosensors providing additional complexity to the signaling pathways. Among several leukocyte-specific integrins, lymphocyte function-associated antigen-1 (LFA-1 or αLβ2; CD11a/CD18) is a key T cell integrin, which plays a major role in regulating T cell activation and migration. Adhesion to LFA-1’s ligand, intracellular adhesion receptor 1 (ICAM-1) facilitates firm endothelium adhesion, prolonged contact with antigen presenting cells (APCs), and binding to target cells for killing. While the downstream signaling pathways utilized by LFA-1 are vastly conserved they allow for highly disparate responses. Here we summarize the roles of LFA-1 and ongoing studies to better understand its functions and regulation.